Social Business Contribution of Grameen Bank Muhammad Yunus in The Development of Poverty Reduction Discourse in Indonesia - Amarta Risna Diah Faza (International Economic and Finance Review, 2022)
This study aims to answer the following question: What role does the Grameen Bank Muhammad Yunus social company play in the development of Indonesia's poverty reduction discourse? This issue is examined utilizing a meta-synthesis method and a systematic literature review employing SALSA (Search, Appraisal, Synthesis, and Analysis) techniques. The data was collected using the Publish or Perish (PoP) tool from Google Sholar's online database between 2000 and 2002. There were 55 articles linked to the social business Grameen bank Muhammad Yunus in Indonesia that were discovered using the keywords available. Only 23 articles are truly relevant to the topic of research on the social business of Grameen bank Muhammad Yunus in Indonesia after going through the article screening step. This research reveals that there has been a lot of discussion in Indonesia concerning Grameen Bank Yunus' social enterprise from diverse perspectives. Researchers have proposed two distinct tendencies. For starters, it is frequently used optimistically. The social business model Grameen bank used in Indonesia can eliminate poverty, according to 91 percent of the 23 papers. Second, it has a gloomy bent. Two MSMEs out of the 23 in this study failed to apply the Grameen Bank social business model. Furthermore, the Grameen Bank Yunus social business model faced criticism, one of which was that it did not follow Islamic shari'ah in practice. Specifically, according to certain Islamic philosophers, adopting an interest-based structure. Specifically, according to certain Islamic scholars, adopting an interesting system that includes riba is practicing usury legislation, which is haram. Nonetheless, the bulk of research findings indicates that Grameen Bank Yunus' social business model has the potential to be employed as one of the options for alleviating poverty in Indonesia.